2019
DOI: 10.1186/s13287-019-1303-0
|View full text |Cite
|
Sign up to set email alerts
|

Generation of pig induced pluripotent stem cells using an extended pluripotent stem cell culture system

Abstract: Background: Pigs have emerged as one of the most popular large animal models in biomedical research, which in many cases is considered as a superior choice over rodent models. In addition, transplantation studies using pig pluripotent stem (PS) cell derivatives may serve as a testbed for safety and efficacy prior to human trials. Recently, it has been shown that mouse and human PS cells cultured in LCDM (recombinant human LIF, CHIR 99021, (S)-(+)-dimethindene maleate, minocycline hydrochloride) medium exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 51 publications
1
64
0
Order By: Relevance
“…Pig iPS cells with doxycyclineinducible piggyBac (PB) expression vectors encoding porcine 4 factors (OSKC) NANOG expression were absent [34]. Our previous work showed that pig PC-iPS with 4 factors (OSKC), NANOG is heterogeneously expressed in LCDMV culture medium [14]. Others report that in pig iPS cells generated by episomal vectors [32] and lentivirus vectors [47] separately containing 6 factors (OKSM+NANOG+LIN28) NANOG is expressed, but exogenous NANOG factor has not been silenced.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pig iPS cells with doxycyclineinducible piggyBac (PB) expression vectors encoding porcine 4 factors (OSKC) NANOG expression were absent [34]. Our previous work showed that pig PC-iPS with 4 factors (OSKC), NANOG is heterogeneously expressed in LCDMV culture medium [14]. Others report that in pig iPS cells generated by episomal vectors [32] and lentivirus vectors [47] separately containing 6 factors (OKSM+NANOG+LIN28) NANOG is expressed, but exogenous NANOG factor has not been silenced.…”
Section: Discussionmentioning
confidence: 99%
“…The pluripotency of NANOG tdTomato knock-in positive PC-iPS cells was corroborated in vitro with the following assays. NANOG knock-in positive PC-iPS cells were positive to AP staining (Additional file 3: Figure S2C), the method of AP staining is reference for our publication data [14]. Clustering analysis showed that knock-in positive PC-iPS cells could be clustered with pig EPS cells [12], but were separate from trophoblast cell (TE), inner cell mass (ICM), and early blastocyst (SB) [43] ( Fig.…”
Section: Verification and Transcriptome Analysis Of Nanog Tdtomato Knmentioning
confidence: 92%
See 3 more Smart Citations